Measuring Attitudes Towards Empirically Supported Treatment in Real World Addiction Services - SILVER WOLF (ADELV UNEGV WAYA), DAVID PATTERSON (2014)
Mental health workers with favorable attitudes toward empirically supported treatments (ESTs) are more likely to break through implementation barriers. The Evidence-Based Practice Attitudes Scale has been shown to be reliable for mental health workers, but has not been validated with addiction workers. This study investigates the use of the scale with a convenience sample of addiction workers from four agencies in one city. Results show that compared to mental health providers, addiction workers were more likely to view ESTs favorably if they were mandated and intuitively appealing. They also tended to rely more heavily on practical experience in forming attitudes toward treatment options. These results may help addiction agencies understand which types of workers are more likely to implement ESTs and inform effective engagement approaches specific to addiction workers.